ENGLISH FOR GENERAL PURPOSES; TEACHING MATERIAL APPROPRIATENESS RESEARCH AT TRIDINANTI UNIVERSITY - Hendrety, Yuyun; Manurung, Jenny Elvinna; Firmansyah, M. Ardhi (English Community Journal, 2024)
This study investigated how lecturers designed their teaching materials and what constraints they encountered in using the materials. It was a qualitative research using a phenomenological design  which involved lecturers of English as general subject at faculties of economic, engineering and teacher training and education as the respondents. To obtain data, the respondents were scheduled  to deliver their responses in semi-structured interview. The findings revealed that the respondents selected their material on the basis of RPS. In order to fulfill students’ need related to the major they have chosen, they used some eBooks of English for Business, Business Communication, Cambridge Online, Bursa Efek Jakarta and English for Engineering to select the material. The respondents realized the importance of integrating four language skills, since the limitation of time some of them focused their teaching on reading skill and vocabulary while some others put much pressure on practicing speaking and writing which they thought more important. Another finding  also revealed that some constraints the respondents encountered during the teaching and learning process were: 1) some students were not very enthusiastic in learning, 2) some students were not confident, they  did not join the class seriously and tended to show low comprehension in learning English, 3) some respondents stated that time allocation in teaching EGP was not enough and  4) they also had not enough time to check or give comment on students’work